JENIS-JENIS TUMBUHAN SEBAGAI SUMBER PAKAN LEBAH MADU Apis cerana Fabr. dan Apis dorsata Fabr. SERTA SUMBANGSIHNYA UNTUK MATERI PLANTAE SMA/MA - Sari, Mike Andam; Zural, Mimin Mardhiah; Jasmi, Jasmi Jasmi (Jurnal Bioconcetta, 2019)
This research has been carried wiht the aims to determine the types of plantsthat can be used as a source of honey bee food which is donated as teachingmaterial for X grade biological material, that is the role of Spermatophyta forlife in the of booklet. This research is research based development. For thefield research descriptive survey method is used while for the research the 4Dmodels is used up to the development stage, that is the validity test. Theresults showed that there 43 species of plants used as honey bee food sources.Identified plants are then donated in the of booklet. The validity test results ofthe booklet design are very valid (95.12%). Then it can be concluded that thetypes of plants as a source of honey bee Apis cerana Fabr. and Apis dorsataFabr., what is used as a very valid teaching material.